Walking With Ears: Altered Auditory Feedback Impacts Gait Step Length in Older Adults - Cornwell, Tara; Woodward, Jane; Wu, Mengnan/Mary; Jackson, Brennan; Souza, Pamela; Siegel, Jonathan; Dhar, Sumitrajit; Gordon, Keith E. (Frontiers in Sports and Active Living, 2020)
Auditory feedback may provide the nervous system with valuable temporal (e. g., footstep sounds) and spatial (e.g., external reference sounds) information that can assist in the control of upright walking. As such, hearing loss may directly contribute to declines in mobility among older adults. Our purpose was to examine the impact of auditory feedback on the control of walking in older adults. Twenty older adults (65–86 years) with no diagnosed hearing loss walked on a treadmill for three sound conditions: Baseline, Ear Plugs, and White Noise. We hypothesized that in response to reduced temporal auditory feedback during the Ear Plugs and White Noise conditions, participants would adapt shorter and faster steps that are traditionally believed to increase mechanical stability. This hypothesis was not supported. Interestingly, we observed increases in step length (p = 0.047) and step time (p = 0.026) during the Ear Plugs condition vs. Baseline. Taking longer steps during the Ear Plugs condition may have increased ground reaction forces, thus allowing participants to sense footsteps via an occlusion effect. As a follow-up, we performed a Pearson's correlation relating the step length increase during the Ear Plugs condition to participants' scores on a clinical walking balance test, the Functional Gait Assessment. We found a moderate negative relationship (rho = −0.44, p = 0.055), indicating that participants with worse balance made the greatest increases in step length during the Ear Plugs condition. This trend suggests that participants may have actively sought auditory feedback with longer steps, sacrificing a more mechanically stable stepping pattern. We also hypothesized that reduced spatial localization feedback during the Ear Plugs and White Noise conditions would decrease control of center of mass (COM) dynamics, resulting in an increase in lateral COM excursion, lateral margin of stability, and maximum Lyapunov exponent. However, we found no main effects of auditory feedback on these metrics (p = 0.580, p = 0.896, and p = 0.056, respectively). Overall, these results suggest that during a steady-state walking task, healthy older adults can maintain walking control without auditory feedback. However, increases in step length observed during the Ear Plugs condition suggest that temporal auditory cues provide locomotor feedback that becomes increasingly valuable as balance deteriorates with age.